MOSQUE FINANCIAL MANAGEMENT IN THE PANDEMIC COVID 19 - Al Bara; Riyan Pradesyah (Proceeding International Seminar of Islamic Studies, 2021)
The financial management of mosques is not something new, but now the community has started to develop it. The mosque's finances were previously only used for mosque operations, but are now starting to be developed. This was done, because of the large number of mosque funds that were not used, and this was what made the community take the initiative to develop these funds to be productive. Research isqualitative research with a descriptive approach. Data collection used is documentation, by collecting literature related to the research theme. The results obtained, that now many mosques are producing funds to help and develop the economy of the community around the mosque. The method used in community economic development is by providing financing to the surrounding community, using sharia principles or a profit sharing system. Then there are those who use the mosque yard to make hydroponic plants, then the plants are sold, and other things.Keywords: Mosque Finance, Mosque Management, Mosque